Self-Initiated Academics Work Adjustment: A Systematic Literature Review - Farah Kalmey (European Scientific Journal, ESJ, 2023)
Expatriation abroad for work and leisure is becoming the norm these days. This necessitates individuals to adjust to life in their new destination and work environment. This paper focuses on presenting a systematic literature review of how the phenomena of Self-Initiated Academics (SIEs) adjust to their work environment. Method: A systematic literature search was conducted by examining articles published in the field of SIE academics. No restrictions were placed on the date of publication because of the nascent nature of the subject of study. The following electronic databases were searched, where language was restricted to only English: Business Source Complete, Academic Search Ultimate, Scopus, Web of Science, and PsycINFO. Result: The result shows that SIEs face challenges that could affect their adjustment to life in a new country, culture, and work. Among these factors are family, local language proficiency, interaction with local hosts and expatriates, prior international work experience, and trainings that are provided at the workplaces. The differentiated treatment of expatriates based on their looks and the passport they hold by the HCNs (host country nationals) is a significant issue that was identified as well.